A new institutional economic analysis of the state and a newi nstitutional economic analysis of the state and agriculture in Sub-Saharan Africa - Kydd, Jonathan G. (International Food Policy Research Institute, 2009)
The state, an all-encompassing term taking in all layers of government from the local to supranational level, is an important actor in most spheres of economic life and is dominant in some. It is a key source of law and has a legal monopoly over the harsher mechanisms of enforcement, such as arrest, prosecution, fining, and loss of liberty. The rules made and upheld by the state are core features of the institutional environment. But the state is also seen as an indispensable provider of certain services, including law and order, physical infrastructure, education and heath, and regulation of the economy, for which it has to raise taxes. There is constant debate about which services the state should provide and the manner of their provision. Economists (both orthodox and those who pursue New Institutional Economics [NIE]) find that the concepts of public goods, market failure, merit goods, and redistribution (Box 20.1) provide useful guidance in this debate, as they focus attention on needs that would not be met adequately, if at all, were provision left solely to the market.